Marginalisasi Perempuan Akibat Pernikahan Siri: Studi Kasus di Kabupaten Soppeng - Muhammad Fadel Adhyputra; Musriadi (USRAH: Jurnal Hukum Keluarga Islam, 2025)
This study raises the phenomenon of marginalization of women due to unregistered marriage in Soppeng Regency, focusing on the causes of unregistered marriage and its impact on women. The research uses a qualitative method with a case study approach and sociology of law, which is supported by two main theoretical frameworks, namely Social Construction of Law Theory and Feminist Legal Theory. Data were obtained through interviews with women who were victims of unregistered marriage, and supported by literature studies and relevant legal documents. The results show that unregistered marriages are triggered by a lack of legal awareness, economic pressure, infidelity, pregnancy outside of marriage, and weak state regulations. As a result, women involved in unregistered marriages experience forms of marginalization in psychological, social, legal and economic aspects. These findings show that patriarchal culture reinforces gender inequality and places women in a vulnerable position. Therefore, systematic interventions are needed through legal education, victim assistance, and strengthening the implementation of regulations to ensure the protection of women's rights in the context of marriage.